Visualization Of The Barong Landung Of The Abiantuwung Tabanan Village In Paintings - Budiana, I Putu; Karja, I Wayan; Budiaprilliana, Luh (CITA KARA : JURNAL PENCIPTAAN DAN PENGKAJIAN SENI MURNI, 2024)
Bali has many types of dances. In Bali you can find many types of dance, such as the barong dance. One of them is Barong Landung, which is the embodiment of a human or giant. With the presence of barong landung, Balinese people interpret it as a force that is believed to provide safety. The research problem focuses on the form of barong landung in the Abiantuwung Traditional Village, Barong Landung has a symbol of connection with Pura Dalem Balingkang. The research uses qualitative methods with analysis of interview and observation data. From the research results, it was found that the Barong Landung in the Abiantuwung Traditional Village is different from the barong landung in general in Bali. Barong landung is the embodiment of the Almighty Creator himself, which undagi in the past was certainly created in accordance with the conditions of the time at that time, namely when intercultural marriage between China and Bali was hot. The charm of this dance can generally only be enjoyed at special moments such as religious holidays in Bali which are usually called Piodalan which are held at certain temples. However, the barong landung in the Abiantuwung Traditional Village is only performed on certain days, such as at certain sasihs where the barong landung goes around at night without lights.